[Lambda] +c production in Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; Ohlson, Alice; et al. (Physics letters, 2019)
A measurement of the production of prompt Λc+ baryons in Pb-Pb collisions at sNN=5.02 TeV with the ALICE detector at the LHC is reported. The Λc+ and …